Microplastics impair amphibian survival, body condition and function. (April 2020) - Boyero, Luz; López-Rojo, Naiara; Bosch, Jaime; Alonso, Alberto; Correa-Araneda, Francisco; Pérez, Javier
Abstract: Microplastics (MPs) are contaminants of increasing concern; they are abundant, ubiquitous and persistent over time, representing potential risks for organisms and ecosystems. However, such risks are still virtually unknown for amphibians, despite the particular attention that these organisms often receive because of their global decline. We examined the effects of MPs (fluorescent, 10-μm polystyrene microspheres) at different concentrations (from 0 to 10 3 particles mL −1 ) on tadpoles of the common midwife toad, Alytes obstetricans, using a microcosm experiment. We assessed MP effects on tadpole feeding, growth and body condition, as well as their ingestion and egestion of MPs (estimated through fluorescence). Additionally, we explored whether MPs became attached to periphyton (the main food source for these tadpoles, thus potentially representing a major way of MP ingestion), and the effect of MPs on periphyton growth (which may translate into altered freshwater ecosystem functioning). Our results showed significant effects on all the examined variables, and caused tadpole mortality at the highest concentration; also, fluorescence indicated the presence of MPs in tadpoles, tadpole faeces and periphyton. This suggests that MPs can be an important source of stress for amphibians in addition to other pollutants, climate change, habitat loss or chytrid infections, and that amphibians can be a major transfer path for MPs from freshwater to terrestrial ecosystems. Graphical abstract: Image 10217 Highlights: MP effects on tadpole feeding, growth and body condition were examined. The highest concentration (1800 part. mL −1 ) caused mortality of most tadpoles. MPs impaired tadpole growth and condition and were found in tadpoles and faeces. MPs attached to periphyton and reduced its growth, affecting ecosystem functioning. Tadpoles most likely ingested MPs while feeding on periphyton.